Primary Nasal Tuberculosis Presenting with Septal Perforation (Janaki Medical College Journal of Medical Science, 2021)
Tuberculosis (TB) is a disease caused by bacteria belonging to the Mycobacterium tuberculosis complex. The disease typically affects the lungs, although, in up to one-third of cases, other organs may also be involved. Extrapulmonary TB occurs in perhaps 15% of all patients with TB. Tuberculosis (TB) is a global health problem with 8 million people infected annually and 3 million people dying from diseases related to its complications. Nasal tuberculosis may be primary or secondary to pulmonary tuberculosis or facial lupus. All of these are rare clinical entities. With the advances in the diagnosis of TB and with even faster and more reliable tests, such as polymerase chain reaction (PCR), its detection almost always requires the performance of invasive procedures, such as fine-needle aspiration or biopsies. The gold standard diagnostic tool is still the culture of mycobacteria which requires a waiting period of more than a month.